Peningkatan Fungsi Manajemen Kerja Praktik dan Pengabdian Masyarakat Melalui Pemeliharaan Aplikasi Web - Ahmad Faris Hisyam Maulana; Tien Fabrianti Kusumasari; Ekky Novriza Alam (AI Society & STMIK Indonesia, 2024)
Universities play a crucial role in developing high-quality human resources through Internship and Community Service Programs, which prepare students with professional skills and relevant competencies. However, implementing these programs often faces issues such as inefficiencies in registration, documentation, and progress reporting. To address these challenges, a university department developed and implemented a comprehensive web-based application system. This research aims to improve and refine the application through software maintenance processes, employing an iterative incremental method with phases including planning, requirements, analysis and design, implementation, testing, and evaluation, conducted repeatedly according to the prioritized order of feature improvements. After being maintained, the application is tested through functional testing using black box techniques and automation tools. Results indicate that the maintenance process successfully ensured the application functions according to established scenarios and requirements, thereby enhancing support for administrative processes of internships and community service programs and overcomes previous management challenges.